Readings in the 20th Century Genocide of the Syriac Orthodox Church of Antioch (Sayfo) - Issa, B.T.; Issa, Theodora; Issa, T.; Issa, Tomayess; Issa, T. (Nova Science Publishers, 2017)
This book, authored by family members who were originated in Mesopotamia, and are members of the Syriac Orthodox Church of Antioch, strives to provide a brief historical background on the Syriac Orthodox Church of Antioch, her dogma, her ancient sacred language (Syriac/Aramaic), and persecution including 1915 Genocide (Sayfo) which might also be referred to as (SAYFO/SEPA/SWORD). This book endeavours to bring to light a historical account of the inhabitants of the ancient land of Mesopotamia, leading to the events that resulted in several persecutions of these original people of the land, specifically during the “Syriac Genocide” (Sayfo) of 1915 (SAYFO/SEPA/SWORD). The authors derive from diverse sources, including some ancient rare manuscripts that have not been, to date, translated into English from Syriac/Aramaic; supported by evidence derived from some of what has been translated into English, including personal accounts. In this book, the authors highlight the number of people who were massacred and those who were forced to leave their Christian faith and convert, including members of the Syriac Orthodox Church of Antioch, showing the unpleasant face of persecution and Genocide against people who are accredited of their huge positive impact on the World’s Civilization. This book commences with a brief historical background on the origin of Christianity in the East, and the historical background of the Syriac Orthodox Church of Antioch, leading to an explanation of the atrocities at the hands of the Ottoman Empire, providing a backdrop to allow an understanding of the context at the time, concluding with some insights of the atrocities in the 21st century against the same people in parts of the Middle East and around the world. The book provides a brief account of the courageous actions taken by patriarchs, other clergy, and lay people to face such atrocities. The authors briefly examine some of the events that took place leading to the main Genocide of 1915, the “Syriac Genocide” (Sayfo) (SAYFO/SEPA/SWORD), or what has been dubbed as “The Forgotten Genocide”. The book concludes with some events that took place in the 21st century which were mainly derived from the ongoing incidents that affected the Syriac Orthodox Church of Antioch and her community in the Middle East and around the world. The image on the front cover of this book is taken from a handwritten manuscript that was written in 1478 in Syriac/Aramaic. This manuscript was the property of the father of the main author and the parental grandfather of the other co-authors, the (Mshamshono Ewangeloyo) “Full Deacon Touma Issa Sr.” (his full name is Touma bar Issa Dbeath Khoshaba Maryya). His vast knowledge in Syriac/Aramaic language, and his reticence in the Syriac Ecclesiastical melodies and hymns led him to teach these two topics for some forty years, thus, and due to his immense knowledge and tireless services to the Holy Syriac Orthodox Church of Antioch, he was ordained by the Archbishop then as a (Mshamshono Ewangeloyo) (i.e. Full Deacon) at the Syriac Orthodox Church of Antioch on 15th July 1901. May his soul rest in peace.